2014
DOI: 10.1097/pas.0000000000000283
|View full text |Cite
|
Sign up to set email alerts
|

Upper Tract Juvenile Polyps in Juvenile Polyposis Patients

Abstract: Patients with juvenile polyposis syndrome (JPS), a hereditary autosomal dominant hamartomatous polyposis syndrome, are at increased risk for colorectal adenocarcinoma. The upper gastrointestinal tract is less often involved by JPS than the colorectum, and, consequently, upper tract juvenile polyps (JPs) are not well studied. We reviewed upper endoscopies and corresponding biopsies in JPS patients documented in our Polyposis Registry. A total of 199 upper gastrointestinal biopsies from 69 endoscopies were avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Although juvenile polyposis is a nonneoplastic lesion, several cases have suggested that it represents a predisposition to gastrointestinal cancer [ 6 8 ]. The risk of gastric cancer in patients with juvenile polyposis was reported to be approximately 11–21% [ 27 ], with a higher risk in patients with a SMAD4 germline mutation [ 28 ]. The current patient had no germline mutations of SMAD4 or BMPR1A , but did have somatic mutations in APC , KRAS , TP53 , and ERBB2 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although juvenile polyposis is a nonneoplastic lesion, several cases have suggested that it represents a predisposition to gastrointestinal cancer [ 6 8 ]. The risk of gastric cancer in patients with juvenile polyposis was reported to be approximately 11–21% [ 27 ], with a higher risk in patients with a SMAD4 germline mutation [ 28 ]. The current patient had no germline mutations of SMAD4 or BMPR1A , but did have somatic mutations in APC , KRAS , TP53 , and ERBB2 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the general population, the JPS has an increased risk of developing cancers such as colorectal cancer ( 16 ). Studies have shown that the incidence of colorectal and gastric cancer in JPS patients is 39% ( 17 ) and 21% ( 18 ), respectively. In addition, pancreatic, duodenal and small bowel cancers also occur in a smaller proportion of patients ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…PGAs are also a manifestation of FAP, including gastric adenocarcinoma proximal polyposis syndrome (GAPPS), a variant 39. Gastric polyps with pyloric differentiation are also found in patients with McCune-Albright syndrome (fibrous dysplasia of bone, café-au-lait skin spots, and precocious puberty; mosaic pattern of germline GNAS mutations40) and even juvenile polyposis 41. Not surprisingly, syndromic (FAP-associated) PGAs arise in younger patients than sporadic examples,22,23,42 developing predominantly in gastric oxyntic mucosa.…”
Section: Stomachmentioning
confidence: 99%
“…39 Gastric polyps with pyloric differentiation are also found in patients with McCune-Albright syndrome (fibrous dysplasia of bone, café-au-lait skin spots, and precocious puberty; mosaic pattern of germline GNAS mutations 40 ) and even juvenile polyposis. 41 Not surprisingly, syndromic (FAP-associated) PGAs arise in younger patients than sporadic examples, 22,23,42 developing predominantly in gastric oxyntic mucosa. At least in western patients, they develop in mucosa without gastritis, often in association with fundic gland polyps.…”
Section: Adenomas and Lesions With Pyloric Gland Differentiationmentioning
confidence: 99%